Single vascular access for concomitant percutaneous coronary intervention and left ventricular assistance with Impella - Lyra, Flávio; O. Almeida, Breno; Mariani Jr, José; A. Lemos, Pedro; Caixeta, Adriano (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Use of the Impella CP left ventricular assist device (LVAD) (Abiomed, Danvers, Massachusetts) requires a 14 French arterial introducer for its insertion, often performed via femoral access. An additional vascular access site is commonly used for coronary angiography or percutaneous coronary intervention (PCI) – in general the contralateral femoral access. The need for multiple vascular access sites requires a longer procedure time and results in an increased risk of vascular complications. Additionally, many patients have associated peripheral vascular disease and therefore limited vascular access. Due to the large diameter of the Impella CP device sheath and its frequent use in high-risk PCI (e.g., complex unprotected left main coronary disease, multivessel disease, cardiogenic shock, advanced left ventricular dysfunction), reducing vascular complications by avoiding a second access is of paramount importance. The shaft diameter of the Impella CP catheter is 9 French, lower than the 14 French of its sheath. As previously reported, there is a novel safe alternative for the placement of an additional sheath up to 7F (1–4) using this available space between the inner diameter of the sheath and the Impella shaft, thereby avoiding the risks of an additional vascular access.